Word Clap Game to Enhance Students' Vocabulary Mastery - Evi Karmila; Mujahidah; Ahdar (Inspiring: English Education Journal, 2020)
This study aims to see the improvement of vocabulary mastery students by using word clap game at the fourth grade of SDN 173 Tiroang Kabupaten Pinrang. The object is IV class which is consisted 25 students. The sample is taken by using classroom random sampling. The design is pre-experimental with pre-test and post-test design and questionnaire to know the students’ respond. The students did the pre-test, got the treatment, did the post-test and questionnaire in the last meeting. Then the criterion of vocabulary mastery of students about noun that consist of three points are memorize, pronounce and writing. It aimed to know whether using word clap game is able to improve students’ vocabulary mastery. The result indicates that there is improvement of the students’ vocabulary mastery. It is indicated by the students’ mean score of post-test (79,52) is greater than pre-test (43,83). Even, for the level significant (p) 5% and (df) = N-1=25-1= 24, and the value of the T- table is 1.710, while the value of t-test is 4.592. It means that, the t-test value is greater than t-table (4.592 ≥ 1.710). Thus, it can be concluded that the vocabulary mastery students is significant better after getting the treatment. The students’ response through the questionnaire by using scale likert also had concluded on the finding, the result showed all the students’ answered positive and most of them got 81-100; the students are very interest in learning English by using word clap game.